Relationship between Angular Measurements and Facial Shape of Young Ivorians with Normal Dental Occlusion - Moussa Diomande; Jean-Bertin Beugre; Mariam Konaté Kady Koueita; Frédéric Vaysse (The Scientific World Journal)
Objective. The aim of this study was to perform an analysis of angular measurements (from both the full face and profile), according to shapes of the human face. Method. It was a descriptive and cross-sectional study of 108 black Ivorian subjects. For each subject selected, two standardized photographs (full face and profile) were taken, followed by anthropometric measurements. The data collected were analyzed using the SPSS 20.0 statistics software for Windows. Results. In the present work, the faces were considered according to three particular qualifiers: broad face, medium face, and narrow face. Thus, 45.37% of the faces in this study were large, 31.48% on average, and 23.15% narrow. The interlabial angles of average face and long face were wider than that of large face with p<0.01. The angle of the facial width was higher for large face and average face, compared to narrow face (p<0.001). Conclusion. Median and bilateral angles lead to rational understanding of the various shapes of the human face.